2018
DOI: 10.1007/s11418-018-1220-z
|View full text |Cite|
|
Sign up to set email alerts
|

Naturally occurring cell adhesion inhibitors

Abstract: This paper reviews naturally occurring cell adhesion inhibitors derived from a plant, microbial and marine origin. Plant-derived inhibitors are classified according to a type of structure. Microbially and marine-derived inhibitors were described according to age. In addition, effects of inhibitors on cell proliferation and that of standards on cell adhesion are listed as much as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…VCAM-1 plays an essential role in mediating the infiltration of leukocytes into tissues ( Takamatsu, 2018 ). We therefore examined whether the VCAM-1 antibody could alter macrophage adhesion and migration to HUVECs in vitro .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…VCAM-1 plays an essential role in mediating the infiltration of leukocytes into tissues ( Takamatsu, 2018 ). We therefore examined whether the VCAM-1 antibody could alter macrophage adhesion and migration to HUVECs in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…VCAM-1, a cell adhesion molecule (CAM), is a transmembrane type I protein that is mainly expressed on ECs during inflammation ( Cook-Mills et al, 2011 ). Previous studies have suggested that VCAM-1 plays an essential role in regulating the inflammatory response and the development of related diseases by mediating the leukocyte adhesion to and infiltration into tissues ( Takamatsu, 2018 ). VCAM-1 gene expression is regulated by multiple transcription factors and cytokines, including NF-kB, Ap-1, SP-1, IL-1β, and TNF-α ( Cook-Mills et al, 2011 ; Lee et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…An array of natural products isolated from plant material (terpenoids, lignans etc. ), or from microbial (efomycine M) or marine origin, have initially demonstrated in vitro inhibition of CAMs, however, no further clinical development can be identified ( 50 ). Employing the rational design-driven approach, a series of glycomimetic inhibitors were derived from the structure of the selectin ligand sialyl Lewis X (sLe X ).…”
Section: Drug Candidates-inhibitors Of Cams: Mabs and Small Moleculesmentioning
confidence: 99%
“…), are macrolides produced by several fungal strains, for example Microsphaeropsis sp. [ 241 ]. These compounds and metabolites from the peribysin group are also detailed in Table 11 .…”
Section: Natural Compounds Of Plant Animal and Fungal Originmentioning
confidence: 99%